The rationale of flexible ICU visiting hours for delirium prevention - Teixeira, Cassiano; Rosa, Regis Goulart (Journal of Emergency and Critical Care Medicine; Vol 2 (October 2018): Journal of Emergency and Critical Care Medicine, 2018)
Delirium is a frequent and severe form of acute brain dysfunction that occurs in the critically ill (1). It currently represents a major challenge for critical care professionals as it is associated with increased mortality, longer intensive care unit (ICU) and hospital stay, increased risk of long-term cognitive impairment, and higher costs of care (2,3). Disappointingly, pharmacologic interventions have a limited role in the prevention and treatment of delirium (4). Conversely, many non-pharmacologic interventions such as reorientation activities, cognitive stimulation, early mobilization, sleep hygiene, and flexibilization of family visits have gained increasing attention due to its low cost and potential to prevent or limit delirium among ICU patients (5,6).